VILLAGE FUND ALLOCATION MANAGEMENT IN IMPROVING COMMUNITY EMPOWERMENT IN JAYASAMPURNA VILLAGE - Aprilianingsih, Shella; Nuraeni, Hikmah; Dewi, Juliyanti; Prameswari, Gladiola; Priyanti, Evi (ipdn, 2024)
As a government directly engaged with the community, villages are the main focus of community empowerment because most of Indonesia's territory is in the countryside. Independent management of village finances through allocating village funds has made villages more independent to achieve a just, prosperous, and prosperous society. In managing the allocation of village funds in Jayasampurna Village, problems such as the need for more community involvement in village fund allocation activities for community empowerment were found. This study uses qualitative methods to produce descriptive data in the form of written or spoken words from people and observed behaviors. This study aims to determine the management of village fund allocation in improving community empowerment in Jayasampurna Village by using the management theory from George R. Terry, which consists of planning, organizing, mobilizing, and supervising. The study results show that the planning indicators are pretty good because they have held a hamlet-level deliberation (MUSDUS). The organization also went well, as seen from the Village Head, who gave directions to the team members. The Jayasampurna Village Government also constantly monitors and evaluates activities that have been realized. However, the mobilization indicators need to be improved because many people are unaware of the village fund allocation program, so the community is less involved. The supervision indicators are also not good because of the lack of socialization regarding managing village fund allocation, so the community is not involved in supervision. Therefore, the Jayasampurna Village government needs to increase transparency and socialization of the program through various media so that the community can be actively involved in supervision and implementation. This step is vital to ensure that allocating village funds is beneficial for community empowerment and improving the village economy.Keywords: Community, Empowerment, Government, Management, Village, Village Fund Allocation